Unveiling the thermal impact of land cover transformations in Khuzestan province through MODIS satellite remote sensing products - Baronian, Iraj; Borna, Reza; Jafarpour Ghalehteimouri, Kamran; Zohoorian, Manijeh; Morshedi, Jafar; Khaliji, Mohammad Ali (Paddy and water environment, 2024)
Land cover, an important element in influencing the Earth's surface climate, has undergone substantial alterations as a result of human activities related to urbanization and industrialization over the past few decades. These changes have had a substantial impact on the Earth's surface temperature and have disrupted the thermal balance. This study specifically investigates how various land cover changes within Khuzestan province influence land surface temperatures, aiming to discern their differential impacts. Using MODIS sensor data, specifically the MCD12Q2 composite product with 17 IGBP classifications for land cover classes and the MODIS surface temperature product (MOD11C3), along with the cross-matrix analysis technique, the study examines the complex relationship between land cover and temperature dynamics. The main land cover types identified in Khuzestan include poor pastures, medium to rich pastures, barren lands, agricultural lands, and urban and residential areas. An in-depth examination of a 20-year trend indicates a notable decline in pastures, coupled with a rise in agricultural and urban areas, and a slight uptick in barren lands. The cross-matrix analysis demonstrates that barren lands and urban/residential zones are the main drivers of elevated land surface temperatures. Throughout the 20-year timeframe, these expanding regions have resulted in an average annual temperature rise of 0.4–0.5 °C in the province. The variations in land surface temperature recorded in 2000, 2010, and 2020 indicate dynamic changes in the thermal characteristics of the selected areas. Initial temperature measurements in 2000 ranged from 26.1 to 31.7 °C, establishing a baseline for subsequent analysis. Over the following years, the areas exhibited diverse temperature trends, with some experiencing significant increases, others maintaining relative stability, and a few showing subtle fluctuations. By 2010, temperatures had generally increased, with readings ranging from 27.2 to 33.1 °C. However, by 2020, the situation became more intricate, with temperatures varying from 28.6 to 32.9 °C. Further investigations confirm that urban/residential areas and barren lands significantly contribute to higher temperature increases compared to other land cover categories. In summary, this study underscores the warming impact of barren lands and urban/residential areas, leading to heightened surface temperatures in Khuzestan province.